PENDUKUNG ANALISA KEPUTUSAN MEDIA PROMOSI PENERIMAAN MAHASISWA BARU UNIVERSITAS BANTEN JAYA MENGGUNAKAN METODE AHP - Ahmad Fatoni; masum masum (Teknik Informatika Fakultas Ilmu Komputer, 2018)
ABSTRAK Decision support systems as a computer-based system consisting of component components include language system components, knowledge system components and problem processing system components that interact with one another. Decision support system is an interactive system, which helps decision makers through the use of data and decision models to solve semi-structured and unstructured problems. AHP is a decision support model developed by Thomas L. Saaty. This decision support model will describe complex multi-factor or multi-criteria problems into a hierarchy, according to Saaty (1993), hierarchy is defined as a representation of a complex problem in a multi-level structure where the first level is the goal, followed by the factor level, criteria, sub criteria, and so on down to the last level of alternatives. With a hierarchy, a complex problem can be broken down into groups which are then arranged into a hierarchical form so that the problems will appear more structured and systematic. From the results of the study showed that the use of Analytical Hierarchy Process (AHP) as a model of decision support system determines the media promotion of new student admission at Banten Jaya University can help the work of the promotion team and the leadership in determining the priority of promotional media that is most appropriate for the promotion through the criteria and alternative weighting process with faster, more accurate and more effective.